Omsk state technical university as an innovative environment for the technical elite - A. . Kosykh (Moscow Polytechnic University, 2022)
The article concerns the main trends of the scientific and educational activity of the university, its achievements for the recent years. The innovative structure of the university ischaracterized as a fundamental for the modern technical education. The article also presents the university development policy as the innovative centre of the Omsk region.